Time course of the uptake of nitrogen, phosphorus, potassium, calcium and magnesium in castor bean (Ricinus communis L.) cultivar 'Campinas' - Nakagawa, Júlio; Neptune, A. M. Louis (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1971)
This research work was carried out on the castor bean crop in order to evaluate the uptake of nitrogen, phosphorus, potassium, calcium and magnesium; and the effects of limestone and fertilizers and the combined effects of both, on uptake of macronutrients mentioned above, plant dry weight and yield. The experiment were conducted in a yellow dark latossol, sandy phase. The maximum uptake period was not well caracterized, but for the treatments which received fertilizers, the greatest uptake for nitrogen, phosphorus, potassium and magnesium was between 41 and 110 days; for calcium, between 41 and 87 days, after sowing. Limestone had no effect on the plant dry weight and yield, but fertilizers increased the uptake of mineral nutrients, plant dry weight and yield.